Kazakhstan in the Eurasian economic union system: opportunities and risks (Journal of Geography and Environmental Management, 2017)
In the article the processes of formation of the largest common market in the CIS, with huge production, scientific and technological potential and enormous natural resources of the Eurasian Economic Union (EEU). In this context, defines the place of Kazakhstan in the EEU, given the growth trends, the development of global processes and changes in the structure of world economic relations. On this basis, it is important to develop new methodology and research methods through the development of a spatial paradigm. The article substantiates the necessity of developing such a paradigm that should be based on the development of regional reconstruction of urban areas and the potential agglomerations, the relevant standards of the post-industrial countries.However, civilizational and technological disparities between the EEU countries do not yet allow to accelerate the economic integration processes, but if they are overcome, drawing on the rich resources of energy and strategic raw materials, the EEU able to make a breakthrough in socio-economic development. Herewith we are talking about spatial categories of the inter-state level similar to the Euroregions In this case, the authors focus on the principles and features of formation not only of inter-state agglomerations, but also the network structures of the population in the border regions of Kazakhstan should be adequate to the Russian economic performance, but not to give them the degree of comfort and infrastructure saturation.